The Effect of Teacher’s Code Switching on Vocabulary Acquisition of Senior High School Students: EFL Learners - M. Sofian Hadi; Lidyatul Izzah; Via Rahma Wati (Universitas Ahmad Dahlan, 2021)
This research is aimed at finding and describing the effect of teacher’s code-switching on vocabulary acquisition of senior high students: EFL Learners the eleven grade students at MAN 2 LEBAK in the academic year of 2020/2021. This research was conducted from January to February 2021. This research was classified as a pre-experimental study. It involved 25 students from one class. The pre-test was given to the participants before the treatment and the post-test was given after the treatment. The data of the pre-test and post- test of the participants were analyzed by using descriptive and inferential statistics. After the data were tested and found the hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. The result of the research shows that the difference in the mean score between the students’ score pre-test and post-test. the score was 7,2, which obtained in the degree of freedom (df) of 23, with the degree of significance 5%, it gained score 1,71387. Which means the t-observation was higher than t-table. It showed that teacher’s code-switching on Students’ vocabulary acquisition is effective.